2019
DOI: 10.1111/os.12553
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the Occipitoaxial Angle and Posterior Occipitocervical Angle in Occipitocervical Fusion

Abstract: ObjectiveTo observe the effects of occipitoaxial angle (O‐C2 angle, OC2A) and posterior occipitocervical angle (POCA) selection on postoperative clinical efficacy and lower cervical curvature in patients with acute acquired atlantoaxial dislocation after occipitocervical fusion (OCF).MethodsA total of 150 healthy subjects without cervical disease (healthy group) were randomly selected based on gender and age. Three spine surgeons measured the OC2A and POCA of the healthy group and averaged the values. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…The POCA is that angle subtended by the tangent to the flat posterior aspect of the occiput between the opisthion and occipital protuberance, and a line drawn along the posterior aspect of the third and fourth cervical facets. An increased POCA reflects a downward head tilt and is associated with increased adjacent segment degeneration due to increased biomechanical stresses [20].…”
Section: The Grabb Mapstone and Oakes Measurementmentioning
confidence: 99%
“…The POCA is that angle subtended by the tangent to the flat posterior aspect of the occiput between the opisthion and occipital protuberance, and a line drawn along the posterior aspect of the third and fourth cervical facets. An increased POCA reflects a downward head tilt and is associated with increased adjacent segment degeneration due to increased biomechanical stresses [20].…”
Section: The Grabb Mapstone and Oakes Measurementmentioning
confidence: 99%
“…• The posterior occipitocervical angle (POCA) is described as the intersection of a tangential line along the flat squamous portion of the occipital bone (from the foramen magnum to the external occipital protuberance) with a line formed by the posterior aspect of the C3 and C4 facets ( Figure 7B). The values of this angle vary from 108.3°± 7.8° and 108.0° ± 8.4°, respectively in males and females [18].…”
Section: Ccj Alignment Anglesmentioning
confidence: 91%
“…• The occipitoaxial angle (C0-C2 McGregor) is determined by the crossing of an oblique line drawn along the inferior endplate of the axis with the McGregor line ( Figure 7B). This angle ranges between 14.8° ± 3.1° in males and 14.2° ± 4.3° in females [18].…”
Section: Ccj Alignment Anglesmentioning
confidence: 93%
“…In contrast, the atlanto‐occipital joint accommodates 25° of flexion and extension and 5° of axial rotation 7 . Significant relationships between the alignments of the upper and subaxial cervical spine have been clearly established in asymptomatic subjects 4, 8 . Several studies demonstrated that atlantoaxial instability can result in compensatory change in subaxial alignment of cervical spine and further lead to spinal degeneration like osteophyte formation, ligamental hypertrophy, and disc space reduction due to the pathological factors related to the instability, including weakness of paraspinal muscles, facetal telescoping, and “listhesis” 4, 9 .…”
Section: Introductionmentioning
confidence: 99%